Reporting of mitotic rate in cutaneous melanoma: A study using the national cancer data base. Issue 3 (March 2017) - Lorimer, Patrick D.; Benham, Emily C.; Walsh, Kendall; Han, Yimei; Forster, Meghan R.; Sarantou, Terry; White, Richard L.; Hill, Joshua S.
Abstract : Background: The seventh edition of the American Joint Commission on Cancer staging manual (AJCC7, published 2009), updated thin cutaneous melanoma staging protocols with the incorporation of mitotic rate (MR). In these patients, higher MR is associated with decreased survival. This study utilizes the National Cancer Data Base (NCDB) to evaluate MR reporting since AJCC7. Methods: The NCDB was queried for patients with primary cutaneous melanoma from 1998 to 2013. Because MR reporting was infrequent prior to implementing AJCC7, records from 2010 to 2013 were analyzed. Categorical variables were compared with chi‐square tests; univariate and multivariate logistic regression models were constructed to determine the effects of covariates on MR reporting. Results: A total of 107, 134 patients met inclusion criteria. From 2010 to 2013, MR reporting increased dramatically (64.3–80.9%). On multivariate analysis, factors significantly related to increased MR reporting include later diagnosis year, T‐classification (T1a and b vs. T1), facility type (academic vs. other specified types of cancer programs), facility volume, patient income, level of education, and county population (metropolitan vs. urban and rural). Conclusions: MR reporting increased dramatically after the introduction of AJCC7; however, disparities in reporting remain across facility types. Further investigation of procedures performed in academic settings that may influence reporting of MR is warranted. J. Surg. Oncol. 2017;115:281–286 . © 2017 Wiley Periodicals, Inc.